Stakeholder Forum activities - Serena Fruttaldo; Roberto Montanari; Petri Mononen; Stig E.R. Franzen; Katia D. Pagle; Andrew Morris; J. Grill; Henar M. Vega; Maria Alonso (2010)
The Deliverable 5.4.2 (Stakeholder Forums activities) is conceived as a report to inform about activities carried out in the Stakeholder Fora. It is conceived as a dynamic document, following progresses in the Stakeholder Forum organization and set up and reporting relevant achievements. It is substantially divided into three sections: The first one, represented by the Executive Summary and the Introduction, is not expected to change during the project life, at least in its core elements; The second one, represented by activities carried out in the Stakeholder Fora (Chapter 1), as general information on specific events, summarizing relevant activities performed in specific events, is supposed to change and be enlarged during the project life, so to provide updates on the activities carried out in Task 5.4.2 – Stakeholder Forum Activities. Next Actions: in Chapter 2 an overview is done on the activities planned to organize the next Stakeholder Fora. Annex 1 presents the Dissemination material to be presented at the General Stakeholder Fora. Annex 2 shows the Dissemination material presented during the TeleFOT First General Stakeholder Forum.